Ações de vigilância e controle da raiva frente a caso positivo em felino no município de Campinas, São Paulo, Brasil - de Lucca, Tosca; Conde Alves Rodrigues, Ricardo; Nitsche, Aline; Bruno von Zuben, Andrea Paula (BEPA. Boletim Epidemiológico Paulista, 2022)
.